Pemanfaatan Sertipikat Hak Atas Tanah Pasca Legalisasi Aset Pada Masyarakat Transmigran Di Desa Sridadi, Kecamatan Buay madang, Kabupaten Ogan Komering Ulu Timur - Tajali, Akief; Pujiriyani, Dwi Wulan; Supriyanti, Theresia (Universitas Mataram, 2025)
This research aims to see how land title certificates are utilized by transmigrant communities who have participated in the PTSL program from 2021 and have businesses. It is hoped that the utilization carried out can increase economic growth for the community. The sample population used as respondents in this research was 30 people. This research uses mixed methods. The data collection method used was a survey method through distributing questionnaires and interviews with community leaders and village officials. The results of this research show that financial literacy in the community has a big impact on the development of businesses run by the community. The financial literacy of the community is quite high. The PTSL program has an impact on the business development of transmigrant communities in Sridadi Village. This can be seen from: 1) changes in the type and number of businesses, 2) changes in business capital, and 3) changes in business management. Business capital owned by the community increases by 50% - 100% of the previous capital. This change in capital is a positive impact of the use of certificates by the community.